The Politics of Education in Iraq: The Influence of Territorial Dispute and EthnoPolitics on Schooling in Kirkuk - Shanks, Kelsey (Journal on Education in Emergencies, 2018)
The Iraqi Disputed Territories, or Disputed Internal Boundaries, consist of 15 districts stretching across four northern governorates from the Syrian to Iranian borders. The oil-rich Iraqi governorate of Kirkuk lies at the heart of this dispute and reflects the country's ethnic and religious diversity. Arabs, Turkmen, Kurds, and Assyrians all claim ancient settlement patterns within the governorate. The symbolic importance of Kirkuk as a homeland to both Kurds and the Turkmen conflicts directly with its strategic importance to Baghdad. While the two linguistically distinct centers of governance vie for control, interethnic communal tensions are rising and questions of identity increasingly overshadow day-to-day life. The existing research on Kirkuk focuses heavily on governance outcomes and possible administrative solutions, but little has been written about the impact of heightened identity politics on the everyday lives of citizens. This paper explores the influence of these conflicts and contests on education in the city of Kirkuk.